2003
DOI: 10.1159/000068479
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Facial Expressions and Emotional Situations in Patients with Dementia of the Alzheimer and Vascular Types

Abstract: The aim of this study was to investigate the ability of patients with dementia to recognize facial expressions and emotional situations. We evaluated 16 patients with dementia of the Alzheimer type (DAT) and 15 with vascular dementia (VD) for general cognition, discrimination of facial expressions and individual faces, and recognition of facial expressions and emotional situations. VD patients performed significantly worse than DAT patients at recognizing facial emotions, even though there was no difference be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…The omission of fear is unexpected when previous studies show that the amygdala is particularly implicated in fear. Likewise, although Shimokawa et al [17] found that AD patients were not as impaired as patients with vascular dementia at recognising facial expressions of emotion, the four emotions chosen were joy, anger, surprise and sadness, but again not fear. Lavenu et al [18], however, found that AD patients were impaired in labelling expressions of fear.…”
Section: Introductionmentioning
confidence: 99%
“…The omission of fear is unexpected when previous studies show that the amygdala is particularly implicated in fear. Likewise, although Shimokawa et al [17] found that AD patients were not as impaired as patients with vascular dementia at recognising facial expressions of emotion, the four emotions chosen were joy, anger, surprise and sadness, but again not fear. Lavenu et al [18], however, found that AD patients were impaired in labelling expressions of fear.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigating emotional processing in dementia patients have focused on the interaction of explicit memory and emotion (Boller et al, 2002;Ikeda et al, 1998;Kazui et al, 2000;Kensinger, Anderson, Growdon, & Corkin, 2004;Moayeri, Cahill, Jin, & Potkin, 2000) or on the recognition of facial expressions of emotions (Kohler et al, 2005;Shimokawa et al, 2003;Roudier et al, 1998;Hargrave, Maddock, & Stone, 2002). Little is known about the acquisition of affective responses in dementia patients, learning processes involving affective content have been addressed by few studies only (Blessing, Keil, Linden, Heim, & Ray, 2006;Hamann, Monarch, & Goldstein, 2002;Hoefer, Allison, Schauer, Neuhaus, Hall, Dang, Weiner, Miller, & Rosen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They found that people with AD performed better than people with vascular dementia on all tasks except in the fourth, even though there was no difference between these two groups of patients in terms of their general cognition and visuoperceptual abilities 11 . Another study suggested that when more subtle emotions were shown, people with AD reported deficits in identifying all emotions 7 .…”
mentioning
confidence: 96%
“…Shimokawa et al suggested that there is a close relationship between intellectual ability and the capacity to recognize emotional situations because without sufficient intellectual ability, it is difficult to comprehend the nature of a given situation or the appropriate emotional state that one would experience in that situation 11 . However, McLellan et al suggested that the general cognitive decline in AD does not seem to present a straightforward relation to the Mini-Mental State Examination (MMSE) or facial expression recognition tasks and that other factors may influence those abilities 12 .…”
mentioning
confidence: 99%